Association of chemical constituents and pollution sources of ambient fine particulate air pollution and biomarkers of oxidative stress associated with atherosclerosis: A panel study among young adults in Beijing, China. (September 2015) - Wu, Shaowei; Yang, Di; Wei, Hongying; Wang, Bin; Huang, Jing; Li, Hongyu; Shima, Masayuki; Deng, Furong; Guo, Xinbiao
Highlights: Particulate chemical constituents associated with oxidative stress are unclear. Metals were the major PM2.5 chemical constituents associated with biomarkers. Iron and nickel were associated with increased oxidized low-density lipoprotein. Calcium was associated with increased soluble CD36. Our findings provide clues for the key pollution components behind oxidative stress. Abstract: Ambient particulate air pollution has been associated with increased oxidative stress and atherosclerosis, but the chemical constituents and pollution sources behind the association are unclear. We investigated the associations of various chemical constituents and pollution sources of ambient fine particles (PM2.5 ) with biomarkers of oxidative stress in a panel of 40 healthy university students. Study participants underwent repeated blood collections for 12 times before and after relocating from a suburban campus to an urban campus with high air pollution levels in Beijing, China. Air pollution data were obtained from central air-monitoring stations, and plasma levels of oxidized low-density lipoprotein (Ox-LDL) and soluble CD36 (sCD36) were determined in the laboratory ( n  = 464). Linear mixed-effects models were used to estimate the changes in biomarkers in association with exposure variables. PM2.5 iron and nickel were positively associated with Ox-LDL ( p  < 0.05). For each interquartile range increase in iron (1-day, 0.51 μg/m 3 ) and nickel (2-day, 2.5 ng/m 3 ), there were a 1.9% [95% confidence interval (CI): 0.2%, 3.7%] increase and a 1.8% (95% CI: 0.2%, 3.4%) increase in Ox-LDL, respectively. We also found that each interquartile range increase in calcium (1-day, 0.7 μg/m 3 ) was associated with a 4.8% (95% CI: 0.7%, 9.1%) increase in sCD36. Among the pollution sources, PM2.5 from traffic emissions and coal combustion were suggestively and positively associated with Ox-LDL. Our findings suggest that a subset of metals in airborne particles may be the major air pollution components that contribute to the increased oxidative stress associated with atherosclerosis.